Fragment-based screening of programmed death ligand 1 (PD-L1). Issue 6 (15th March 2019) - Perry, Evan; Mills, Jonathan J.; Zhao, Bin; Wang, Feng; Sun, Qi; Christov, Plamen P.; Tarr, James C.; Rietz, Tyson A.; Olejniczak, Edward T.; Lee, Taekyu; Fesik, Stephen
Graphical abstract: Abstract: The PD-1 immune checkpoint pathway is a highly validated target for cancer immunotherapy. Despite the potential advantages of small molecule inhibitors over antibodies, the discovery of small molecule checkpoint inhibitors has lagged behind. To discover small molecule inhibitors of the PD-1 pathway, we have utilized a fragment-based approach. Small molecules were identified that bind to PD-L1 and crystal structures of these compounds bound to PD-L1 were obtained.